Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Menggunakan Metode MOORA (Studi Kasus: PT. Zuwar Haramaen Zahra Fahira) - Muhamad Akif Farhat (Universitas Lampung, 2026)
PT. Zuwar Haramaen Zahra Fahira still conducts employee performance appraisal manually, causing the appraisal process to take a relatively long time, potentially creating assessor subjectivity, and increasing the risk of calculation errors. These conditions may lead to inconsistent appraisal results and make it difficult for the company to determine the best-performing employee. This study aims to develop a web-based Decision Support System using the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method to support a more objective and structured employee performance appraisal process. The study employed a quantitative approach with the Waterfall development model. Data were collected through observation, interviews with the HR department, and literature study. The criteria used were discipline, responsibility, work quality, and productivity with weights of 0.25, 0.25, 0.30, and 0.20, respectively. The system was developed using PHP and MySQL. The results indicate that the system is able to perform normalization, weighting, optimization value calculation, and ranking automatically, making the appraisal process faster, more objective, and computerized. Based on the MOORA calculation, alternative A3 obtained the highest optimization value of 0.3600 and ranked first. Black Box testing showed that all system functions operated according to user requirements. Therefore, the developed system can be used as a decision support tool in the employee performance appraisal process at PT. Zuwar Haramaen Zahra Fahira.